The Potential of Crude Extract Bromelain Enzyme on Production of Virgin Candlenut Oil (VCdO) - Sahfitri W. Nasution; Firman Sebayang; Juliati B. Tarigan (Jurnal Akademika Kimia, 2022)
Virgin Candlenut Oil (VCdO) is carried out enzymatically without using high-temperature heating and does not use organic solvents so it produces an oil with good quality and low FFA levels. Bromelain enzyme is sourced from pineapple hump. This study aims to determine the optimal conditions of the characteristics of VCdO including yield and free fatty acid (FFA) levels. Analysis of the fatty acid composition of VCdO was characterized by Gas Chromatography (GC). The manufacture of VCdO was carried out using 3 parameters, namely variations in time, temperature, and the amount of catalyst (enzyme). Optimization of the yield and FFA levels was determined by the response surface method (RSM) based on the Box-Behnken experimental design with 3 factors and carried out as many as 15 experiments. The optimum yield of VCdO was 51.12% at 37 ℃, 34 hours, and enzyme volume 28 mL. The lowest level of FFA VCdO was obtained at 1.213% at 37 ℃, 12 hours, and enzyme volume 23 mL. The results of VCdO analysis with GC showed that the highest fatty acid content was linoleic acid at 43.73%. The FFA levels have obtained the quality standard of candlenut oil according to SNI 01 -4462 -1998.